Development of Toddlers’ Smartphone Flow State Scale: Parent Report Form - Mikyong Byun (MDPI AG, 2021)
Toddlers come into contact with smartphones by the time they are 10 months old, and smartphones eventually become a part of the daily lives of toddlers because they are used as parenting tools and are also attractive toys. Routine exposure to these electronic devices may lead to excessive immersion, which can cause smartphone dependence when toddlers grow up. Based on Csikszentmihalyi’s concept of flow, we aimed to develop a new scale to measure the flow phenomenon in toddlers who are exposed to smartphones. We attempted to identify the constituent factors of a toddler’s flow in smartphones through a literature review, observations, and interviews. Initially, 32 questions were screened from the field verification stage and interviews; the final 20 questions were selected by combining technical statistics, exploratory factor analysis, and expert feasibility. We also found five eligible constituent factors, namely, a playfulness-oriented experience, reaction limited by concentration, and intentional pursuit to achieve the goal, assimilate into the virtual world, and acquire desire-fulfilling skills. We then performed a confirmatory factor analysis on our parent-reported toddlers’ smartphone flow state scale. To secure the criterion-related validity, the correlation between our scale and the preexisting smartphone dependence measurement tool for toddlers was evaluated. Cronbach’s α value of the toddlers’ smartphone flow state scale was 0.95 (each factor was verified as 0.79–0.92 and the explanatory power was 72.21%). The test–retest reliability was found to be stable with the intraclass correlation (ICC) coefficient value of 0.78 (p < 0.001). Our research findings suggest that this novel smartphone flow state scale for toddlers could be a valid and reliable tool for measuring how toddlers feel the flow phenomenon while using smartphones. Furthermore, our results could contribute to the development and evaluation of the interventions that prevent side effects from smartphone overflow in toddlers.